1970
DOI: 10.4314/ejhs.v28i4.12
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Pattern and Factors Associated with Blood Pressure and Fasting Plasma Glucose Control among Patients with Type 2 Diabetes Mellitus in Police Referral Hospital in Ethiopia

Abstract: BACKGROUND: The prevalence of T2DM in Ethiopia is on the rise according to certain studies. Appropriate management approaches are required to achieve desired goals of therapy in the clinical setup. This study was conducted to assess the treatment pattern and the factors associated with BP and FPG control among patients with T2DM in Federal Police Referral Hospital.METHOD: An institution based cross sectional study was conducted from 15th October 2016 to 15th January 2017. A Systematic random sampling technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 26 publications
2
17
1
Order By: Relevance
“…Evidence from the interviews and focus groups we have undertaken, previous findings [ 11 , 12 , 13 , 60 ], feedback from the co-design workshops, and the context of the hospital enabled identification of the health problem. We identified that improving the effectiveness of type 2 diabetes management for patients with type 2 diabetes was the specific problem existing at the diabetes centre of TASH.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Evidence from the interviews and focus groups we have undertaken, previous findings [ 11 , 12 , 13 , 60 ], feedback from the co-design workshops, and the context of the hospital enabled identification of the health problem. We identified that improving the effectiveness of type 2 diabetes management for patients with type 2 diabetes was the specific problem existing at the diabetes centre of TASH.…”
Section: Resultsmentioning
confidence: 96%
“…Ineffective management of type 2 diabetes has been associated with poor clinical outcomes, which include disease progression, and increased health services utilisation, such as repeated hospitalisations and high all-cause mortality [ 5 , 6 , 7 ]. In Sub-Saharan Africa (SSA) [ 8 , 9 , 10 ] including Ethiopia [ 11 , 12 , 13 ], there exists a high rate of diabetes-related morbidity and mortality, high cost of diabetes care, and poor quality of life for patients with type 2 diabetes. Excessive levels of diabetes-related problems and high cost of type 2 diabetes care in SSA are attributed to widespread lack of treatment success, stemming from inadequate organisational involvement and delivery of care [ 8 , 9 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Four studies found that the presence of comorbidities was associated with poor glycaemic control [53,75,77,87]. The presence of hypertension lead to poor glycaemic control in one study [16].…”
Section: Clinical Factorsmentioning
confidence: 99%
“…Eight studies assessed the relationship between the female gender and glycaemic control [18,29,34,51,61,64,65,73], two studies found that the female gender was associated signi cantly with poor glycaemic control [18,34] versus one study that linked it to good glycaemic control [29]. Male gender in respect of glycaemic control was assessed by eleven studies [27,31,39,44,58,66,75,77,83,85,87], two studies associated it with good glycaemic control [58,75], while two studies linked it to poor glycaemic control [27,87]. Fifteen studies assessed the relationship between educational level and glycaemic control, in one study, primary, secondary, or tertiary education levels were associated with good glycaemic control [29].…”
Section: Sociodemographic Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation